Coal Pore Structure Evolution Under Drying–Wetting Cycle - Liu, Yikang; Wang, Haiyan; Niu, Huiyong; Xing, Shuwen; Wang, Gongda; Zhou, Zhenxing; Yang, Yanxiao; Liu, Xiaolu (Natural resources research (New York, N.Y.), 2025)
The process of dry–wet cycling in coal mining areas exerts a more pronounced degrading effect on coal pores compared to prolonged water immersion, and it enhances the tendency of coal spontaneous combustion. To investigate the fractal characteristics of coal during dry–wet cycling and the evolutionary changes in its overall pore structure, various pore properties were analyzed using scanning electron microscopy, CO2 adsorption, low-temperature N2 adsorption, and mercury intrusion porosimetry. The results revealed that with post dry–wet cycling, coal exhibited increased porosity and rougher surface texture. Notably, the apparent porosity of coal after secondary dry–wet cycling reached 24.68. While the type of coal pores remained unchanged across different aperture ranges, there was noticeable increase in cumulative pore volume within the 100–220 nm and 1000 nm aperture segments. Moreover, the primary drying–wetting cycle coal demonstrated the highest cumulative pore-specific surface area and volume within the 0–100 nm pore size range. Interestingly, the drying–wetting cycle did not lead to the formation of micropores in the < 2 nm section; instead, it facilitated the gradual transformation of micropores into mesopores and increased the likelihood of their further evolution into macropores. These findings provide a valuable theoretical basis for the prevention and control of drying–wetting cycle of coal spontaneous combustion disasters and environmental pollution caused by the strategy and increasing the tendency of coal spontaneous combustion. The research results provide theoretical guidance for preventing and controlling water-immersed air-dried coal.